ChemInform Abstract: Synthesis, Structure, and Magnetic Characterization of Cr4US8. Issue 12 (March 2016) - Ward, Matthew D.; Chan, Ian Y.; Malliakas, Christos D.; Lee, Minseong; Choi, Eun Sang; Ibers, James A.
Abstract: Cr4 US8 is prepared by reaction of a 1:1:6 molar mixture of U, Cr, and S in a PbI2 flux (1073 K, 12 h; 75% yield).